Supraspinal inhibitory effects of chimeric peptide MCRT on gastrointestinal motility in mice. (16th June 2017) - He, Chunbo; Li, Hailan; Zhang, Jing; Kang, Yanping; Jia, Fang; Dong, Shouliang; Zhou, Lanxia
Abstract: Objectives: Chimeric peptide MCRT, based on morphiceptin and PFRTic-NH2, was a bifunctional ligand of μ- and δ-opioid receptors (MOR-DOR) and produced potent analgesia in tail-withdrawal test. The study focused on the supraspinal effects of morphiceptin, PFRTic-NH2 and MCRT on gastrointestinal motility. Moreover, opioid receptor antagonists, naloxone (non-selective), cyprodime (MOR selective) and naltrindole (DOR selective) were utilized to explore the mechanisms. Methods: Intracerebroventricular administration was achieved via the implanted cannula. Gastric emptying and intestinal transit were measured to evaluate gastrointestinal motility. Key findings: (1) At supraspinal level, morphiceptin, PFRTic-NH2 and MCRT significantly decreased gastric emptying and intestinal transit; (2) MCRT at 1 nmol/mouse, far higher than its analgesic dose (ED50 = 29.8 pmol/mouse), failed to regulate the gastrointestinal motility; (3) MCRT-induced gastrointestinal dysfunction could be completely blocked by naloxone and naltrindole, but not affected by cyprodime. Conclusions: (1) Morphiceptin and PFRTic-NH2 played important roles in the regulation of gastrointestinal motility; (2) MCRT possessed higher bioactivity of pain relief than gastrointestinal regulation, suggesting its promising analgesic property; (3) MCRT-induced motility disorders were sensitive to DOR but not to MOR blockade, indicating the pain-relieving specificity of speculated MOR subtype or splice variant or MOR-DOR heterodimer.